POLA KEMITRAAN ANTARA ASOSIASI PENGEMBANGAN INDUSTRI KERAJINAN RAKYAT INDONESIA (APIKRI) DENGAN PENGRAJIN MITRA DI KABUPATEN BANTUL, YOGYAKARTA - Wahyudi (FP AGRI 16 UMY 046, 2016)
This research aims to determine the partnership pattern and objective conducted by APIKRI together with the craftsmen partner in Bantul as well as to recognize benefits and constraints obtained by the craftsmen, perception of craftsmen partners towards the pattern and the achieved goals during the partnership process run by APIKRI. The method applied in this research is descriptive analysis by defining respondents based on the census of all craftsmen partners placed in Bantul. In addition, data were collected through interviews and observation which resulted that the partnership pattern conducted by APIKRI is unbound partnership included in the general pattern of trade partnerships with the purpose of supporting the craftsmen in terms of marketing and developing the craftsmen’s skills in the craft industry. The perceived benefits are in accordance with craftsmen’ expectation as the beginning of that partnership, except several obstacles faced by some craftsmen still cannot be resolved. Craftsmen’s perception towards the partnership pattern categorized as good which means that the executed partnership is in accordance with the needs of both parties. Moreover, the perception of craftsmen to achieve the partnership’s objectives is included in the unfavorable category which means there are several things that are less useful for the craftsmen partners.